Unique challenges in management alcoholic hepatitis with large left sided ischiorectoal abscess- A case report - Vasavada, Bhavin; Patel, Hardik (Journal of Society of Surgeons of Nepal, 2022)
Alcoholic hepatitis is a condition with high mortality and morbidity. It is routine to have infectious complications with alcoholic hepatitis. However, ischiorectal abscess with its unique management challenges has not been described in the literature. We describe here a case of ischiorectal abscess with alcoholic hepatitis, and how the post-operative course is much more complicated due to underlying alcoholic hepatitis.